Competency Models for High-Tech Sectors: A Systematic Review - Farinha, C.; Duarte, A.P.; Rosa, M. (EAWOP - European Association of Work and Organizational Psychology, 2025)
Emerging technologies, such as the Internet of Things and artificial intelligence, are accelerating shifts in high-tech sectors, where workforce competencies must adapt quickly to meet industry demands. These high-tech fields, in particular, face rapid advancements and volatility in required skill sets, necessitating that companies redefine employee competencies to maintain competitive advantage. In response to these dynamic shifts, competency models in HR management are essential for aligning talent development with industry requirements, offering a structured framework to define the knowledge, skills, and abilities, that employees need to effectively support organizational strategy. Despite the increasing importance of these models, a significant gap exists in the literature concerning the specific skills required in high-tech sectors amidst digital and global changes. The purpose of this systematic literature review is to analyse and synthesize existing research on competency models tailored to high-tech sectors, focusing on how these models can better support HR professionals in adapting workforce skills to meet the fast-paced demands driven by technological advancements. By conducting a systematic review, the study aims to address gaps in the current understanding of competency requirements specific to high-tech environments, providing clarity on relevant skills. A comprehensive search was conducted in the Scopus and Web of Science database using defined search terms. Screening with strict inclusion and exclusion criteria resulted in 39 peer-reviewed articles published in the last decade. Findings emphasize the balance of hard and soft skills necessary in high-tech fields, where technical expertise must blend with strong interpersonal and adaptive capabilities to keep pace with rapid industry changes. However, existing literature is dense and lacks synthesis, hindering practical application. To provide clarity, this review proposes organized approaches for developing competency models, such as skills and competencies taxonomies to support HR professionals in high-tech sectors with actionable insights into competency adaptation for a swiftly evolving workforce.